2007
DOI: 10.1136/jcp.2007.049825
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal follicular lymphomas share common characteristics with mucosa-associated lymphoid tissue lymphomas

Abstract: Results suggest that duodenal follicular lymphomas have intermediate characteristics of MALT lymphomas and nodal follicular lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 34 publications
(25 reference statements)
5
62
1
1
Order By: Relevance
“…1,2 On the other hand, we have also reported that duodenal FLs harbor t(14;18)(IGH-BCL-2), exhibit ongoing somatic hypermutations, and express CD10 and B-cell lymphoma 2 (BCL-2), which are common features of nodal FL. However, the proteins have roles in somatic hypermutation in duodenal FL have not yet been identified.…”
mentioning
confidence: 99%
“…1,2 On the other hand, we have also reported that duodenal FLs harbor t(14;18)(IGH-BCL-2), exhibit ongoing somatic hypermutations, and express CD10 and B-cell lymphoma 2 (BCL-2), which are common features of nodal FL. However, the proteins have roles in somatic hypermutation in duodenal FL have not yet been identified.…”
mentioning
confidence: 99%
“…Patients with grade 3 follicular lymphoma were excluded from this study since these cases are typically managed as diffuse large B cell lymphoma [31] . A subset of the 80 patients examined were also subjects of our previous studies [33][34][35][36] . Of the 80 patients identified, 30 were excluded since they did not undergo 18F-FDG-PET.…”
Section: Methodsmentioning
confidence: 99%
“…Polymerase chain reaction was performed according to standard procedures as described previously. [19][20][21][22] The primers used for immunoglobulin heavy chain gene amplification were as follows: [19][20][21] The primers used for T-cell receptor gamma gene amplification were as follows. 22 for …”
Section: Polymerase Chain Reaction For Detecting Immunoglobulin Heavymentioning
confidence: 99%